Analysis of Factors That Influence Senior High School Students' Interests and Decisions to Study Abroad. Case Study: International Foundation Course (IFC) in Indonesia and Malaysia - Lia Margaret Silalahi; Meutia Meutia; Andriyansah Andriyansah (Dinasti International Journal of Management Science, 2023)
This research aims to (1) determine the influence of intrinsic motivation on senior high school students' interest in studying abroad (2) determine the influence of family support on senior high school students' interest in studying abroad (3) the influence of organizational commitment on senior high school students' interest in studying abroad (4) determine the influence of intrinsic motivation on senior high school students' decision making to study abroad (5) determine the influence of organizational commitment on senior high school students' decision making to study abroad (6) determine the influence of students' interest in studying on senior high school students' decision making to study abroad (7) determine the effect of government support as a moderating variable on senior high school students' interest and decision making to study abroad in the International Foundation Course program. The research design used in this research is a case study research design. Variables in this research include intrinsic motivation, family support, organizational commitment, government support, interest in learning and decision making. The population in this study were all students who took part in the IFC program by PDVL. The sample in this study was 112 respondents taken using the purposive sampling method with the Partial Least Square (PLS) analysis technique. The results of the study concluded that (1) intrinsic motivation has a significant effect on senior high school students' interest in studying abroad (2) family support has a significant effect on senior high school students' interest in studying abroad (3) organizational commitment has a significant effect on senior high school students' interest in studying abroad ( 4) intrinsic motivation has a significant influence on senior high school students' decision making to study abroad (5) organizational commitment has a significant influence on senior high school students' decision making to study abroad (6) interest in learning has a significant influence on high school students' decision making to study abroad (7) Government support as a moderating variable has a significant effect on high school students' interest and decision making to study abroad in the International Foundation C.ourse (IFC) program